2019
DOI: 10.7717/peerj.6500
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex activity in permeabilised cells of chronic fatigue syndrome patients using two cell types

Abstract: Abnormalities in mitochondrial function have previously been shown in chronic fatigue syndrome (CFS) patients, implying that mitochondrial dysfunction may contribute to the pathogenesis of disease. This study builds on previous work showing that mitochondrial respiratory parameters are impaired in whole cells from CFS patients by investigating the activity of individual mitochondrial respiratory chain complexes. Two different cell types were used in these studies in order to assess individual complex activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Instead of impaired glycolytic capacity driving the shift in metabolism, our results suggest that the change may be driven by elevated usage of alternatives such as the β oxidation of fatty acids. Fatty acid utilization rates were previously reported to be unchanged in permeabilized ME/CFS lymphocytes [41]. However, the permeabilization process (with loss of cytoplasmic cellular context, e.g., metabolites) or the metabolic quiescence and greater death rates of ME/CFS lymphocytes may have obscured the result in this previous study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Instead of impaired glycolytic capacity driving the shift in metabolism, our results suggest that the change may be driven by elevated usage of alternatives such as the β oxidation of fatty acids. Fatty acid utilization rates were previously reported to be unchanged in permeabilized ME/CFS lymphocytes [41]. However, the permeabilization process (with loss of cytoplasmic cellular context, e.g., metabolites) or the metabolic quiescence and greater death rates of ME/CFS lymphocytes may have obscured the result in this previous study.…”
Section: Discussionmentioning
confidence: 51%
“…Previous steady state measurements and metabolic flux measurements of mitochondrial respiratory function in ME/CFS lymphocytes have suggested that in ME/CFS cells there is either a generalized reduction [6][7][8] or little change [9,15] in mitochondrial activity and respiratory capacity. However, functionally normal OXPHOS Complex I to IV activity has also been reported in ME/CFS lymphocytes [11,41], while the expression of mitochondrial proteins is upregulated in patient saliva, platelets and lymphocytes [12,13,23]. Elevated nonmitochondrial ATP production has also been reported in ME/CFS lymphocytes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of impaired glycolytic capacity driving the shift in metabolism, our results suggest that the change may be driven by elevated usage of alternatives such as the  oxidation of fatty acids. Fatty acid utilization rates were previously reported to be unchanged in permeabilized ME/CFS lymphocytes [47]. However, the permeabilization process (with loss of cytoplasmic cellular context eg metabolites) or the metabolic quiescence and greater death rates of ME/CFS lymphocytes may have obscured the result in this previous study.…”
Section: One Of the Key Upstream Regulators Of Mitochondrial Protein mentioning
confidence: 53%
“…Previous steady state measurements and metabolic flux measurements of mitochondrial respiratory function in ME/CFS lymphocytes have suggested that in ME/CFS cells there is either a generalized reduction [6][7][8] or little change [9,15] in mitochondrial activity and respiratory capacity. However, functionally normal OXPHOS Complex I to IV activity has also been reported in ME/CFS lymphocytes [11,47], while the expression of mitochondrial proteins is upregulated in patient saliva, platelets and lymphocytes [12,13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Dennis et al showed that the 4E-BP1 phosphorylation was inhibited when intracellular adenosine triphosphate (ATP) levels were lowered (48). Interestingly, chronic fatigue has previously been associated with a decrease in cell metabolism (15,18,49,50), and PBMCs of CFS patients showed a decrease in mitochondrial function compared to PBMCs of HC when stressed (51)(52)(53). Axis inhibition protein (AXIN1), negatively regulates the Wnt signalling pathway by downregulation of β-catenin (54), but has also been identi ed as a scaffold protein that activates TGF-β signalling (55).…”
Section: Discussionmentioning
confidence: 99%